Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1515/jpm-2020-0352
|View full text |Cite
|
Sign up to set email alerts
|

Causal analysis of fetal death in high-risk pregnancies

Abstract: Objectives To determine the causes of fetal death among the stillbirths using two classification systems from 22 weeks of gestation in a period of three years in high-risk pregnancies. This is a retrospective observational study. Methods The National Institute of Perinatal Health in Mexico City is a Level 3 care referral center attending high-risk pregnancies from throughout the country. The population consisted of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In agreement with the results of this study, E . coli , Staphylococcus and Listeria were identified as pathogens present in the amniotic space in an investigation of the role of infections in stillbirths [ 48 ]. Additionally, a prospective study comparing the umbilical cord microbiomes of stillbirths and livebirths found six taxa uniquely present in stillbirths; of these, Bacteroides was the only taxon common within the findings of this work [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the results of this study, E . coli , Staphylococcus and Listeria were identified as pathogens present in the amniotic space in an investigation of the role of infections in stillbirths [ 48 ]. Additionally, a prospective study comparing the umbilical cord microbiomes of stillbirths and livebirths found six taxa uniquely present in stillbirths; of these, Bacteroides was the only taxon common within the findings of this work [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…By using the ICD-PM, these studies facilitate essential insight into perinatal death causes and helped raise global awareness of perinatal mortality and the complexity of classifying its causes. The ICD-PM is currently considered the gold standard and is often favoured over other classification tools because it facilitates the lowest rate of unspecified causes and because it is the only tool that classifies death by time of death and separates maternal and foetal conditions into two entities [21][22][23]25,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…This leads to inconsistent classification and globally incomparable data. For example, a growth restricted foetus of a mother with pre-eclampsia dies due to asphyxia following a placental abruption before labour, can be classified as A3 'antepartum hypoxia', A4 'Other specified antepartum disorder', or A5 'Disorder related to foetal growth' [29][30][31].…”
Section: Reported Challenge Case Example or Explanation Suggested Ame...mentioning
confidence: 99%
“…A study from a tertiary care centre in Mexico considered placental and/or fetal infection as probable cause of death in 15.1% of stillbirths. The pathogens identified were E. coli, Staphylococcus warnerii, Enterobacter spp., Klebsiella pneumoniae, Listeria monocytogenes, M. tuberculosis, C. albicans, Candida krusei, CMV, and Zika virus [166].…”
Section: Stillbirthmentioning
confidence: 99%